Analysis of the Fastest Cost and Route Using the Graph Theory and Network Analysis - Dewi Rahmawati; Marsela Putri; Rosmawati; Farhanul Hakim (Universitas Islam Indonesia, 2023)
Samarang is one of the subdistricts in the Garut Regency with the most tourism potential. According to 2021 data from Garut Statistics Indonesia, the tourism potential in the Samarang included nature tourism, cultural tourism, special interest tourism, and artificial tourism. Nature tourism had the highest proportion of approximately 49.15% compared to other tourism. Still, there is limited access to these tourist sites due to considerable distance, damaged road conditions, and remoteness from settlements. This research aims to determine the optimal route, cost, and travel time to access the tourist location. Based on this, the methods used were graph theory and network analysis methods. The distance determination was done using Google Maps and quantitative analysis. The results showed that the shortest distance to access tourist sites in the Samarang from the center of Garut city was about 15.55 km, required the cost of IDR132,000, and travel duration of 52 minutes. At the same time, the results of the network analysis method revealed that the normal route was around 21.35 km, which cost IDR158,000 and required a travel time of 66 minutes.